On the identity of Polydamas and Glaucus in Themistius Or. 1,7b (Minerva, 2018)
Themistius, in Or. 1,7b, mentions two characters named Glaucus and Polydamas. The different translators of the discourse have systematically identified them with Homeric homonyms, by putting forward arguments that are not at all convincing. This identification does not agree with the idea that Themistius tries to defend in the text, where he argues that anger is a dangerous feeling, especially when it occurs in a powerful person. The suggestion posed in this paper, supported by the testimonies of various Greek authors, contents that Themistius is not refering to two Homeric warriors, but to Polydamas of Skotoussa and Glaucus of Carystus, two famous pugilists.
Keywords: Themistius; Polydamas; Glaucus; Homeric warriors; pugilists